Analisis Watermarking Citra Digital Berbasis Contourlet Transform dan DCT dalam Ruang Warna RGB, YCbCr, dan YIQ - Daniel Setiadikarunia; Agus Setiawan (Jurnal Telematika, 2025)
This article discusses watermarking techniques for contourlet transform (CT)-based digital images, combined with the discrete cosine transform (DCT). Watermarks are inserted into one of the colour components of the host image's colour space, namely RGB, YCbCr, or YIQ. Level 2 contourlet transformation is applied to the colour component used for watermark insertion. The upper-right subband of the contourlet transform result is selected, divided into 4×4 blocks, and then DCT and zigzag scanning are applied to each block. The watermark used is a black-and-white (binary) image. To improve security and reduce spatial correlation, the watermark is scrambled using Arnold scrambling. The watermark is embedded in the host image by inserting a PN sequence corresponding to each watermark bit into the midband DCT coefficients of the 4×4 block. Test results show that the inserted image has a high level of imperceptibility (PSNR> 30 dB). The watermark is robust against JPEG compression with a minimum quality factor of 8, scaling of 75% and 125%, rotation of 180°, cropping of 20% with different cropping positions, and the addition of up to 5% Gaussian noise, but is not robust against 90° rotation and median filtering. Watermarks embedded in the YCbCr colour space in the Cb or Cr components, or in the YIQ colour space in the I or Q components, achieve optimal imperceptibility and robustness.